An Efficient Protocol for the Green and Solvent-Free Synthesis of Azine Derivatives at Room Temperature Using BiCl3-Loaded Montmorillonite K10 as a New Recyclable Heterogeneous Catalyst. (8th October 2012) - Ravi, K.; Krishnakumar, B.; Swaminathan, M.
Abstract : A new BiCl3 -loaded montmorillonite K10 catalyst has been prepared by solid dispersion method and was characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and cyclic voltammetry (CV) measurements. BiCl3 loaded K10 (BiCl3 -K10) has been used as solid acid catalyst for the synthesis of azine derivatives from benzophenone hydrazone and ketones/aldehydes by simple physical grinding. This BiCl3 -K10 gives an excellent yield with short reaction time and is an inexpensive, easily recyclable catalyst for this reaction.